Magnetic Saturation Suppression of Common-Mode Choke Coil by Selecting Suitable Inverter Carrier Frequency - Hasegawa, Kohei; Tokiwa, Tsuyoshi; Kobayashi, Shinji; Takamatsu, Seisho; 光平, 長谷川; 常盤 豪; 伸次, 小林; 誠昇, 高松 (IEEJ JOURNAL OF INDUSTRY APPLICATIONS, 2022)
Common-mode choke (CMC) plays an important role in suppressing the leakage current produced during the operation of pulse width modulation (PWM) inverters. However, when the common-mode path exhibits a large series stray capacitance, particularly the capacitance produced by long shielded cables, the CMC core reaches magnetic saturation. This paper presents a technique of selecting a suitable carrier frequency for the inverter to suppress the magnetic saturation of the CMC. First, the analytical approach leads to a non-saturation condition, and clarifies the maximum and minimum carrier frequency design conditions. Subsequently, the effect of the design is demonstrated by a non-linear circuit simulation and experimental tests using an actual inverter system demonstrate the effectiveness of the design technique.